The Effect of Mulching on the Biological and Physical Properties of Soil in Maize - Modiba Maimela, Maxwell; Hanaa Tharwat, Mohamed Ibrahim; Simon, Barbara; Dekemati, Igor (Journal of Central European Green Innovation, 2022)
To study the effect of different mulching levels on the physical and biological properties of the soil. A field experiment was conducted in Gödöllő Szárítópuszta of the Hungarian University of Agriculture and Life Sciences experimental farm (Pest county). The experiment was laid down in a random block design with five treatments, namely M0%= control, M25%= 25%, M50%= 50%, M75%= 75%, and M100%= 100% level of mulch cover. Soil moisture content (SMC), soil penetration resistance (SPR) and earthworm abundance were measured. SMC, SPR and earthworm abundance were taken at 15-day intervals unless the weather prevented sampling. The experiment was set up from May 2019 until September 2019. The statistical data was carried out using one-way variance analysis with Tukey HSD (Honestly Significant Difference) multiple comparisons post hoc tests. The significance level used in the statistical studies was 5%. Mulch treatments improved water significantly in the first two months (June and July) of crop growth at 10 and 20 cm, however, moisture was not conserved for too long. Mulch treatment did not affect penetration resistance in all treatments. SPR was high after July in all the treatments due to low SMC. The measured SPR reached 5.3 MPa in August in M25%. The highest earthworm abundance was measured at M100% in August while the lowest was measured in control treatments. The grain yield was highest at M50% (1704 kg/ha) compared to the control. Mulch treatments were assessed based on factors such as soil moisture content, biological activity and penetration resistance and mulch was partially found to be advantageous.
Keywords: mulching; soil moisture content; soil penetration resistance; earthworm abundance; maize